Hubungan Antara Kualitas Interaksi Pengasuh dengan Kepercayaan Diri Anak Usia 4-5 Tahun di TK Negeri Pembina Kota Timur - Retmi Sukri; Nurulaeni Laide; Fitriyani Muharam; Sri Hikmawati Dali; Sadrila Mokoagow; Sulastya Ningsih (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This study aims to describe the relationship between the quality of caregiver–child interaction and the level of self-confidence among early childhood students at TK Negeri Pembina Kota Timur. The interaction quality assessed in this research includes aspects of attention, warmth, responsiveness, and support provided by caregivers throughout the children’s learning activities. A quantitative approach, employing a descriptive–correlational method, was used to obtain measurable insights into the relationship between the two variables. Data were gathered through direct observation and questionnaires distributed to teachers and parents, then analyzed using descriptive statistics and correlation techniques. The findings indicate that the quality of caregiver interaction falls into the good category, as reflected in the average score of 13.3. The results for children’s self-confidence also fall under the good category, with an average score of 9.5. This indicates that children are beginning to show greater courage in speaking, express their opinions more openly, and demonstrate initiative during classroom activities. The comparison between the two variables reveals a tendency that more positive caregiver interactions are associated with higher levels of children’s self-confidence. These results emphasize that warm, responsive, and consistent interactions play a crucial role in fostering self-confidence in early childhood, highlighting the importance for caregivers and teachers to maintain communication patterns and emotional support that align with the developmental needs of young children.